Full Chain Analysis and Comparison of Gas-Fired Power Plants with Co2 Capture and Storage with Clean Coal Alternatives - Nie,Z; Korre,A; Durucan,S (Energy Procedia, 2013)
This paper presents the new models developed for the natural gas fuelled power generation chain, involving various natural gas production methods, gas processing routes, gas transport options, and alternative gas based power generation with/without CO2 capture. The comprehensive and quantitative Life Cycle Inventory (LCI) database developed models inputs/outputs of processes at high level of detail, allowing to account for technical and geographic differences in the power generation value chain scenarios analysed. With the advantage of LCI models developed at unit process level, this work successfully identified the key operational parameters for alternative gas-fuelled power plants and the key component processes that emit the majority of GHGs across the gas supply chains.